Parliamentary Representation: A Cross-national Study of Candidates' Views. Issue 3 (13th March 2019) - Sudulich, Laura; Trumm, Siim; Bridgewater, Jack
Abstract: This study explores political elites' self-conceptualisation of parliamentary representation by using data on nearly 7000 candidates encompassing 18 elections in 15 countries. We examine the relevance of institutional features, closeness to the sources of representatives' mandates, party family, as well as candidates' personal characteristics, with a modelling strategy that accommodates the understanding of role orientation as a two-stage process. We posit that choosing between being loyal to a party or to voters is not equivalent to prioritising one's own agency in the first place, and suggest that self-conceptualisation of parliamentary representation happens in two different stages. We find that individual-level characteristics such as gender and ideological proximity to one's party, but also party family, play a key role in shaping views on authority versus independence. The effects of political environment and institutions are limited to shaping a choice between responding to one's party or constituents.